Integrating Human Reliability Assessment into Health Promotion Strategies to Reduce Patient Mortality and Preventive to Legal Issue - S. Zulfikar. G. Assegaf; Suardi AL; Jerny Dase; Annisa Anwar Mutaher; Berty. J Nelwan; Andi Alfian Zainuddin; Gatot. S. Lawrence (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Human error is one of the leading factors in medical negligence cases worldwide. These errors may include a range of actions such as misdiagnosis, medication errors, and procedural mistakes. Based on studies and reports from several major hospitals in Indonesia, as well as reports from the Hospital Patient Safety Committee (Komite Keselamatan Pasien Rumah Sakit – KKPRS), incidents related to patient safety in the ICU remain considerably high. Human Reliability Analysis (HRA) is a method used to prevent human error by analysing and assessing the likelihood of human mistakes within a work system and by developing mitigation strategies to minimise such errors. The HRA method involves several techniques and approaches that can be applied in healthcare settings to enhance patient safety and prevent medical negligence. Methods: This qualitative descriptive-exploratory study was conducted in the ICU of Dr. Wahidin Sudirohusodo General Hospital from January to March 2025. Thirty ICU healthcare workers were recruited through total sampling. Mortality data were reported only for contextual description, not as a direct outcome of HRA, in order to avoid conflating qualitative error mapping with quantitative outcomes. Results: ICU nurses demonstrated a higher potential for human error compared to anesthesiology residents. The ICU mortality rate was 45%, with chronic kidney disease, malignancies, and cardiovascular disorders identified as the leading causes of death. These figures are presented descriptively and not interpreted as effects of HRA Conclusion: The SHERPA approach provided insight into potential errors, their impact, and contributing factors, enabling recommendations to strengthen ICU safety systems. These findings underline the urgent need for medical audits and suggest potential implications of SHERPA in reducing medico-legal risks, rather than establishing causal effects on mortality reduction.